2016
DOI: 10.4062/biomolther.2015.172
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Regulates Apoptosis and Adhesion in Hs578T Triple-Negative Breast Cancer Cells

Abstract: Amygdalin, D-mandelonitrile-β-D-glucoside-6-β-glucoside, belongs to aromatic cyanogenic glycoside group derived from rosaceous plant seed. Mounting evidence has supported the anti-cancer effects of amygdalin. However, whether amygdalin indeed acts as an anti-tumor agent against breast cancer cells is not clear. The present study aimed to investigate the effect of amygdalin on the proliferation of human breast cancer cells. Here, we show that amygdalin exerted cytotoxic activities on estrogen receptors (ER)-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 34 publications
3
36
0
2
Order By: Relevance
“…Immunoblot analysis was performed as described previously (23). Protein extracts in lysis buffer [50 mM Tris, 2% sodium dodecyl sulfate (SDS), 1 mM ethylenediaminetetraacetic acid (EDTA) and 0.1 M dithiothreitol) containing protease inhibitor cocktail (Roche Diagnostics GmbH, Mannheim, Germany) were subjected to 12% SDS-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis was performed as described previously (23). Protein extracts in lysis buffer [50 mM Tris, 2% sodium dodecyl sulfate (SDS), 1 mM ethylenediaminetetraacetic acid (EDTA) and 0.1 M dithiothreitol) containing protease inhibitor cocktail (Roche Diagnostics GmbH, Mannheim, Germany) were subjected to 12% SDS-polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Chang et al found that the expression of Bax and the caspase‐3 enzyme activity were increased while the expression of Bcl‐2 was decreased in DU145 and LNCaP cells after amygdalin treatment, leading to PCa cell apoptosis. Lee et al determined the expression levels of apoptosis‐related proteins in breast cancer cells, which treated with amygdalin at various concentrations, and found that amygdalin increased the expression of pro‐apoptotic protein Bax and decreased that of antiapoptotic Bcl‐2 and pro‐ Caspase‐3. At the same time, PARP cleavage was observed in breast cancer cells treated with amygdalin.…”
Section: The Basic Antitumor Mechanisms Of Amygdalinmentioning
confidence: 99%
“…Amygdalin is a cyanogenic glucoside derived from seeds of rosaceous plants, for example seeds of bitter almonds (Prunus dulcis), or apricot, cherry, apple, peach, plum, etc. [4,5,6,7]. Amygdalin C 20 H 27 NO 11 , is composed of one molecule of benzaldehyde, two molecules of glucose and one molecule of hydrocyanic acid [8].…”
mentioning
confidence: 99%